DIFFERENTIAL CELL COUNT AS DIAGNOSTIC AND PROGNOSTIC MARKER OF ACUTE MYOCARDIAL INFARCTION - Sri Anita; Liong Boy Kurniawan; Darwati Muhadi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Myocardial infarction is a necrosis of myocardial cells due to lack of blood and oxygen supply caused by obstruction of coronary arteries, mostly due to atherosclerosis processes. Increased inflammatory marker level is associated with poor cardiovascular prognosis. This study was aimed to know whether leukocytes count, differential cell count and the Ratio of Neutrophils-Lymphocytes (RNL) could distinguish between types of Acute Myocardial Infarction (AMI) and to evaluate its correlation with mortality. This was a cross-sectional retrospective study using medical records patients which were diagnosed as AMI by clinicians in Cardiac Centre of the Dr. Wahidin Sudirohusodo Hospital during the period of April 1st, 2015 - May 31st, 2016. Statistical analysis used the Mann-Whitney and Chi-Square test, p<0.05 was considered as significant. The total subjects were 435 patients divided into 289 ST- Elevation Myocardial Infarction (STEMI) and 146 Non-ST-Elevation Myocardial Infarction (NSTEMI). There were significant differences in that mean of leukocytes, neutrophils, lymphocytes, monocytes, eosinophils counts and RNL between STEMI and NSTEMI (p <0.05). Significant differences were also found in leukocyte, neutrophils, lymphocytes, eosinophils, basophils and RNL mean between those who died and survived (p <0.05) and a significant correlation between increased leukocytes, neutrophils, basophils counts with mortality (p <0.05). In conclusion, the number of leukocytes and leukocyte count can be used as diagnostic markers of AMI between STEMI and NSTEMI, as well as prognostic markers among patients who died and survived. Routine blood sampling cohort studies in patients with AMI can avoid the bias of the results obtained.